Manufacturing influences on microstructure and fracture mechanical properties of polycrystalline tungsten. (December 2019) - Conte, M.; Aktaa, J.
Highlights: Fracture toughness tests of two different tungsten plates with two orientation in the brittle and semi brittle regime. Fracture surface analysis by scanning electron microscope (SEM). Crack path analysis by light microscope. Abstract: Polycrystalline tungsten is a promising candidate for future fusion applications as plasma facing material due to its good thermophysical properties at high temperatures. Fracture mechanical properties of sintered and rolled, commercially available polycrystalline tungsten are characterized taking into account the strong anisotropy due to different grain shape and orientation with respect to the rolling direction. The fracture mechanics investigations are accompanied by fractographic analyses of two tungsten plate grades with varying cold working ratios of two different manufacturers (PLANSEE SE, Austria and A.L.M.T Corp., Japan). In this respect three point bending tests (3-PB) with sub sized fracture mechanical specimens in different orientations of the anisotropic microstructure are performed at three temperatures, ranging from 25 °C to 400 °C at a deflection rate of 2 µm s − 1 . In addition, crack initiation and crack growth mechanisms depending on texture and cold working ratio are investigated by means of scanning electron microscopy (SEM).